Total arthroplasty in ankylosed knees: a case series - Gilberto Luiz Camanho (Clinics, 2009)
OBJECTIVE: To present nine patients with ankylosis in their knees that were submitted to a total arthroplasty to lessen their pain and improve their functional limitation. For these patients, arthrodesis remained a possibility in the event of arthroplasty failure. INTRODUCTION: Ankylosis of the knee is a severe functional limitation that becomes worse when pain is present. Arthrodesis of the knee is a classical indication for such patients, since it resolves the pain; however, the severe functional limitation remains. METHODS: In the present study, we evaluated the clinical course of nine patients who underwent total arthroplasty of the knee, and were followed up for at least five years. RESULTS: The results demonstrate that all of the patients experienced a significant reduction in pain and some improvement in the degree of knee flexion and extension. CONCLUSION: Based on the latest follow-up, there has been no need to perform arthrodesis for any of our patients, showing that a total arthroplasty could be a option for treatment in knee ankylosis.